Identifying the prevalence and correlates of multimorbidity in middle-aged men and women: a cross-sectional population-based study in four African countries. Issue 3 (14th March 2023) - Micklesfield, Lisa K; Munthali, Richard; Agongo, Godfred; Asiki, Gershim; Boua, Palwende; Choma, Solomon SR; Crowther, Nigel J; Fabian, June; Gómez-Olivé, Francesc Xavier; Kabudula, Chodziwadziwa; Maimela, Eric; Mohamed, Shukri F; et al.
Abstract : Objectives: To determine the prevalence of multimorbidity, to identify which chronic conditions cluster together and to identify factors associated with a greater risk for multimorbidity in sub-Saharan Africa (SSA). Design: Cross-sectional, multicentre, population-based study. Setting: Six urban and rural communities in four sub-Saharan African countries. Participants: Men (n=4808) and women (n=5892) between the ages of 40 and 60 years from the AWI-Gen study. Measures: Sociodemographic and anthropometric data, and multimorbidity as defined by the presence of two or more of the following conditions: HIV infection, cardiovascular disease, chronic kidney disease, asthma, diabetes, dyslipidaemia, hypertension. Results: Multimorbidity prevalence was higher in women compared with men (47.2% vs 35%), and higher in South African men and women compared with their East and West African counterparts. The most common disease combination at all sites was dyslipidaemia and hypertension, with this combination being more prevalent in South African women than any single disease (25% vs 21.6%). Age and body mass index were associated with a higher risk of multimorbidity in men and women; however, lifestyle correlates such as smoking and physical activity were different between the sexes. Conclusions: The high prevalence of multimorbidity in middle-aged adults in SSA is of concern, with women currently at higher risk. This prevalence is expected to increase in men, as well as in the East and West African region with the ongoing epidemiological transition. Identifying common disease clusters and correlates of multimorbidity is critical to providing effective interventions.